Women's Hijab, A Conflict between Morteza Motahari and Qasim Amins Views - Yahya bouzarinejad; Mahdi Yazdani (زن در فرهنگ و هنر)
Qasim Amin was a prominent Egyptian intellectual who, through his two writings, initiated numerous social reforms in Egypt. These reforms were subsequently replicated in other Islamic countries. He initially expressed his personal opinions regarding the position of women in society and their hijab in a manner that was sympathetic to Islam. However, he eventually began to express his own views that were not in accordance with Islam. He regards the hijab worn by eastern women as the cause of regression in eastern countries, while the lack of hijab worn by western women is the source of progress in western countries. He also maintains that the hijab worn by women stimulates and intensifies the desire of men. He was of the opinion that women are subject to four historical periods, and when they reach the fourth period, they have achieved complete liberation, similar to communism. He believed that the hijab was a form of sex slavery and that it was only appropriate for the women of the Prophet. He also held the belief that hijab is a consequence of the interaction between Islamic countries and their neighboring countries. These are merely a few of the issues that Amin addressed in his two renowned works, Tahrir al-Mur'a and al-Mur'a al-Jadidah, regarding hijab. In this article, we compare Amin’s perspectives on the hijab with those of Morteza Motahari. Amin will be provided with appropriate responses in accordance with Morteza Motahari’s comments. The impact of Western modernity and the role that Westerners have depicted for women is evident in Amin. Amin’s works are primarily focused on the development of gender, with a particular emphasis on women’s education and the notion that women's independence is a precursor to Western civilization. He considers the hijab from the perspective of Islamic jurisprudence, but ultimately reaches his own personal opinions regarding the hijab and pursues complete freedom from it.